1987
DOI: 10.2134/agronj1987.00021962007900030005x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Hail Research in Sunflower: Defoliation1

Abstract: Accurate loss procedure and compensation due to hail losses are a major concern to both the producer and the insurance company. Field experiments simulating leaf loss such as that which would occur as a result of a hail storm were conducted on hybrid sunflower (Helianthus annuus L.) at Carrington and Fargo, ND. The objective of this study was to investigate the agronomic response of sunflower to various levels of defoliation applied at different stages of plant development. Defoliation treatments (0, 25, 50, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 3 publications
3
26
1
3
Order By: Relevance
“…At GS R6, full leaf display has occurred and removal of leaves is complete without the possibility for development of small uncounted leaves as is the case at GS R1 where even at 100% defoliation perhaps 10 or more small leaves could develop after treatment. Schneiter et al (1987) showed 48 and 82% yield reductions from 100% defoliation at GS R1 and R6, respectively, for Hybrid 894. They observed the greatest yield reduction when defoliation was applied at GS R3 and R4 where the majority of plants died at 100% defoliation.…”
Section: Exp 3 Effects Of Defoliation and Growth Stage On Dwarf Sunmentioning
confidence: 97%
See 1 more Smart Citation
“…At GS R6, full leaf display has occurred and removal of leaves is complete without the possibility for development of small uncounted leaves as is the case at GS R1 where even at 100% defoliation perhaps 10 or more small leaves could develop after treatment. Schneiter et al (1987) showed 48 and 82% yield reductions from 100% defoliation at GS R1 and R6, respectively, for Hybrid 894. They observed the greatest yield reduction when defoliation was applied at GS R3 and R4 where the majority of plants died at 100% defoliation.…”
Section: Exp 3 Effects Of Defoliation and Growth Stage On Dwarf Sunmentioning
confidence: 97%
“…Yield was also reduced by the 50 and 75% defoliation levels at the 15 leaf to flowering stages. Schneiter et al (1987) studied sunflower response to defoliation by utilizing a conventional height hybrid where treatments were applied at defined maturity stages. Schneiter reported a significant growth stage by defoliation interaction where yield reductions increased with increasing defoliation and maturity until stage R4.…”
mentioning
confidence: 99%
“…Os poucos trabalhos sobre simulação de danos foliares por granizo, ou mesmo por insetos, para culturas, como para o próprio girassol (BUTIGNOL, 1983;KARADOGAN;AKGÜN, 2009;MORIONDO;ORLANDINI;VILLALOBOS, 2003;MURO et al, 2001;NEZAMI et al, 2008;SCHNEITER;JONES;HAMMOND, 1987), utilizam a desfolha artificial de folhas inteiras como metodologia, o que não reflete o dano físico em área proporcional de todas as folhas, com suas consequências no transporte de assimilados, água e demais nutrientes e estresse fisiológico (TAIZ;ZEIGER, 2004). Trabalhos que relacionam a injúria foliar e a estimativa de perdas de área fotossintetizante na forma de escala para quantificação dos danos foliares por granizo não foram relatados na literatura.…”
Section: Introductionunclassified
“…Dessa forma, pode-se inferir que a metodologia de desfolha artificial utilizada para a avaliação e estimativa de dano foliar por granizo (KARADOGAN; AKGÜN, 2009;MORIONDO;ORLANDINI;VILLALOBOS, 2003;MURO et al, 2001;SCHNEITER;JONES;HAMMOND, 1987) pode não ser a mais adequada.…”
Section: Introductionunclassified
“…Three different types of responses to plant defoliation have been described (McNaughton, 1983): (1) detrimental effect, which consists of a decrease of growth rate and fitness of attacked plants; (2) no effect, when attacked plants show similar growth rates and fitness to control plants unless a certain damage threshold is reached above which a negative effect occurs; (3) beneficial effect, when, after moderate level of damage, a recovery in plant growth and fitness is observed (Prins et al, 1989). On the other hand, Schneiter et al (1987) and Schneiter and Johnson (1994) pointed out that (a) defoliation affects yield and (b) its occurrence in different developmental stages results in significant differences in final yield.…”
Section: Introductionmentioning
confidence: 99%